Photocatalysis of ethanol oxidation by tetrachloroferrate(III) supported on Dowex 2‐X8. (15th October 2014) - Schembri, Laura; Hoggard, Patrick E.
<x xml:space="preserve">Abstract</x> FeCl4− heterogenized on a Dowex 2‐X8 anion exchange resin catalyzes the photooxidation of ethanol to acetaldehyde under visible and near‐UV irradiation (>345 nm). The rate of reaction is proportional to the oxygen partial pressure up to 1 atm. Oxidation is suggested to occur through the formation of 1‐hydroxyethylhydroperoxide, initiated by the photodissociation of a chlorine atom. The hydroperoxide re‐oxidizes the iron(II) species, both the oxidation and reduction steps producing acetaldehyde. This mechanism is consistent with the increases in yield with ethanol concentration in ethanol–toluene mixtures towards an asymptotic limit. Copyright © 2014 John Wiley & Sons, Ltd.